STRATEGI PENGEMBANGAN POTENSI WISATA RELIGI DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT ( Makam Ahmad Bin Abdullah bin Tholib Al Alathas Sapuro) - Dwi Edi Wibowo; Arum Ardianingsih; Nurul Huda; Mutimatun Ni’ami (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2023)
Tourism plays a key role in boosting economic growth, improving prosperity and reducing poverty. Pekalongan city has great opportunities for religious tourism i.e. sightseeing at the Tomb of Ahmad bin Abdullah bin Tolib al-Arasas. â€¢ Religious tourism at the tombs of al-Arathas, ie religious tourism has great opportunities. Religious travel is a journey aimed at gaining pleasure, satisfaction and knowledge. Religious tourism can lead to mosques, great figures, historical figures, or tombs of figures. The purpose of this study was to analyze strategies for developing religious tourism potential and the impact of religious tourism on improving the economy of communities. The research method is a qualitative analysis using the SOAR analysis method, that is, an analysis that identifies internal and external factors. In this case, the author analyzes strategies for developing religious tourism potential. Based on the research results, the first conclusion is that four alternative strategies, namely SA strategy (strengths and aspirations), OA strategy (opportunities and aspirations), SR strategy (strengths and consequences), and OR (opportunities) strategy. Second, the existence of religious tourism is evidenced by an increase in UMKM and a decrease in unemployment, as well as the opening of new jobs.Â Keywords: Strategy, religious tourism, economy